Obese patients and robotic colorectal surgery: systematic review and meta-analysis - Suwa,Y; Joshi,M; Poynter,L; Endo,I; Ashrafian,H; Darzi,A (BJS Open, 2020)
BackgroundObesity is a major health problem, demonstrated to double the risk of colorectal cancer. The benefits of robotic colorectal surgery in obese patients remain largely unknown. This metaanalysis evaluated the clinical and pathological outcomes of robotic colorectal surgery in obese and nonobese patients.MethodsMEDLINE, Embase, Global Health, Healthcare Management Information Consortium (HMIC) and Midwives Information and Resources Service (MIDIRS) databases were searched on 1 August 2018 with no language restriction. Metaanalysis was performed according to PRISMA guidelines. Obese patients (BMI 30 kg/m2 or above) undergoing robotic colorectal cancer resections were compared with nonobese patients. Included outcome measures were: operative outcomes (duration of surgery, conversion to laparotomy, blood loss), postoperative complications, hospital length of stay and pathological outcomes (number of retrieved lymph nodes, positive circumferential resection margins and length of distal margin in rectal surgery).ResultsA total of 131 fulltext articles were reviewed, of which 12 met the inclusion criteria and were included in the final analysis. There were 3166 nonobese and 1420 obese patients. A longer duration of surgery was documented in obese compared with nonobese patients (weighted mean difference −21·99 (95 per cent c.i. −31·52 to −12·46) min; P < 0·001). Obese patients had a higher rate of conversion to laparotomy than nonobese patients (odds ratio 1·99, 95 per cent c.i. 1·54 to 2·56; P < 0·001). Blood loss, postoperative complications, length of hospital stay and pathological outcomes were not significantly different in obese and nonobese patients.ConclusionRobotic surgery in obese patients results in a significantly longer duration of surgery and higher conversion rates than in nonobese patients. Further studies should focus on bette